Pengaruh Disiplin Kerja dan Pemberian Insentif Terhadap Kinerja Karyawan PT. Nusantara Card Semesta ( studi kasus karyawan divisi sales dan marketing Jakarta) - Tri Handoko; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2017)
The company is part of the Organization, an organization must be able to deceive its employees. The company's activity on the pemberdayaaan leading to the objectives of the company through the development of its human resources is good and will bring progress for the company, therefore, efforts to improve the performance of employees is a challenge the company's most serious because of the success to achieve the goal and the survival of the company depends on the quality of the performance of its employees. This study examines the performance of employees at PT. Nusantara Card Semesta sales and marketing division of Jakarta which are obtained from the respondents, to do with the discipline of work and granting of incentives.The purpose of this research is to know how the discipline of work and granting of incentives on performance of employees of PT. Nusantara Card Semesta Division salesand marketing. This research type is explanatory research. The technique of sampling using a method using saturated. As for the number of samples taken as many as 40 of the respondents i.e. all employees.Based on the results of the descriptive analysis, showed the results of research that the discipline of working in a high category of 65.0%. Variable grant of incentives on the category quite well, as big as a variable and 40.0% performance in the categories high, amounting to 60.0%, Multiple correlation coefficient calculation based on yield value 0.729 which means have a strong correlation. Based on the calculation of the coefficient of determination indicates that the variable is the discipline of work and granting incentives contributed to the influence of 53.2% against the performance of employees.Suggestions in this study was to give the award to employees in the form of praise,salary increases, job promotion, or granting allowances to employees who have been doing work with full discipline. the company is expected to provide an adequate incentive because the granting of incentives can lead to high motivation for employees for Moreover, necessary supervision against employees so that employees can work in a good and up.